Imaging Characteristics of Retinoblastoma: A Single Tertiary Care Center Experience from Pakistan - Marya Hameed, Fatima Siddiqui, Wajid Hussain, Hina Hanif, Kanchan Shewak Ram, Samra Saleem, Ashok Kumar, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Retinoblastoma is a rare tumor of eye in the pediatric population. It is seen in every 15000-18000 births with no gender or racial predilection. Retinoblastoma can have a variable presentation ranging from leukocoria to a mass in the eye. Aim: To provide physicians a snapshot of different modes of presentation. This study employs the data from computed tomography (CT) and magnetic resonance imaging (MRI) and analyzing it for frequency of different presentations from a radiological point of view. Methods: This was a retrospective cross-sectional study carried out at the National Institute of Child Health (NICH) which is the largest tertiary care pediatric center in Karachi, Pakistan. Records of children from 1 month to 16 years who were diagnosed with retinoblastoma between March 2021 to March 2022 were accessed from the database and assessed. The collected data was then analyzed on SPSS 26. Results: The most frequent presentation noted was leukocoria followed by vision loss, swelling, pain and redness. Calcification was the most frequently reported feature in CT scan whereas retroglobular involvement was mostly seen in MRI scans. Chi square showed a statistically significant correlation between age at presentation with presenting symptoms (p=0.04) and sellar involvement (p=0.00). Additionally, statically significant association was seen between family history and laterality in our study. Conclusion: MRI is the recommended modality due to its sensitivity and superior soft-tissue resolution. CT scan is superior to MRI in detecting calcifications. In developing countries due to a lack of proper facilities and awareness, there is a disparity in the prognosis and presentation of retinoblastoma. Bilateral tumors are most commonly heritable and patients presenting with tumors in both eyes are recommended a through genetic workup. Keywords: Retinoblastoma, ocular tumor, leukocoria, red eye, Magnetic resonance imaging, computed tomography